Conflict resolution in Libya - Harrak Srifi, Yasser (Open Science Journal, 2023)
This paper examines the role of key conflict elements such as solidarity among disagreeing groups and partisan foreign intervention in the complexification of the Libyan conflict. Incorporating evidentiary events along with a comparative application of different conflict theories (ripeness theory, instrumentalism, primordialism, protracted social conflict and constructivism), this paper argues that ideational factors top merely material factors in the Libyan conflict and no permanent solution can be achieved without changing people 's socially constructed identities and world view.